SPECIFIC IMMUNOGLOBULINS FOR INTRAVENOUS INJECTION IN PEDIATRIC PRACTICES - A.L. Zaplatnikov (Union of pediatricians of Russia, 2007)
The article presents information on the protective and therapeutic efficiency of specific immunoglobulins for intravenous injection. The author gives a characteristics and provides regimes of medication dosage of specific immunoglobulins for intravenous injection used among children.Key words: specific immunoglobulins for intravenous injection, children, treatment.